Human-Robot Interaction: Changes in Perception Towards a Socially Assistive Robot by Variating the Anthropomorphism Level in Cardiac Rehabilitation Scenario (2021)
Several studies have shown the positive impact of the use of a social assistance robot (SAR) in cardiac rehabilitation (CR) programs. However, SARs carry significant ethical risks associated with their anthropomorphic characteristics.